Adhesion‐controlled anisotropic rotational molding of multilayered ultrasoft silicone films - Kaufmann, Anke; Schlicht, Samuel; Rösel, Uta; Drummer, Dietmar (Polymer Engineering and Science, 2024)
Rotational molding allows the manufacturing of geometrically complex, hollow parts while maintaining low tool costs. While the rotational molding of thermoplastics is subject to inherent limitations regarding the wall thickness and processing of ultrasoft materials, the present paper introduces the adhesion-controlled, highly dynamic rotational molding of room-temperature curing resins, enabling the fabrication of thin, multilayered films and anisotropic, ultrasoft silicone components at rotational speeds up to 2000 min−1. The studies comprise the influence of the applied rotational speeds and the different molds. Based on scanning electron micrographs, the process is shown to allow for locally tailored part thicknesses, enabling the manufacturing of multilayered films with singular layers obtaining thicknesses below 10 μm. Relying on the control of emerging centripetal forces, the rotational speed depicts a quasi-linear influence on resulting layer thicknesses, allowing for controlling the film thickness with excellent interlayer bonding. Relying on the superposition of consecutive layers, the adhesion-controlled process allows for tailoring emerging nonlinear, ultrasoft stress–strain behaviors across a broad range of desired moduli. Conducting compression tests, increased rotational speeds are shown to reduce the part stiffness, attributed to the increased relative influence of interlayer interfaces, allowing for reproducing mechanical characteristics similarly found in ultrasoft human soft tissue.<br